The richness of evaluation in school, an unhidden treasure - Muriel, Luz Enid; Gómez, Luz Stella; Londoño-Vásquez, David Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article provides some reflections about: the evaluation potential that is found in the diverse school experiences of the students; the importance of defining the evaluation purpose from its ethical dimension; and how, thanks to evaluation, it is possible to provide visibility for the construction of learning by transcending the conception of evaluation as a measurement and quantification instrument. Therefore, a relation is established between some daily situations in the educational environment and the characteristics of evaluation as a resource, the ethical principles that govern the evaluation, and the needs of the younger generations for the consolidation of a new world available for them, which allows for the development of their cognitive, creative, affective, and social potential.